The Effect of Contextual Teaching and Learning Approach and Learning Creativity on Student Learning Outcomes - Andi Erni Ratna Dewi Dewi; Andi Aminullah Alam (Journal of Educational Science and Technology (EST), 2021)
The purpose of this study was to determine the effect of the contextual teaching and learning approach and learning creativity on student learning outcomes. This type of quantitative research with an expost facto approach involved 95 students who were selected by purposive sampling. Data analysis through classical assumption test and multiple linear regression analysis. The results showed that the Contextual Teaching and Learning Approach and learning creativity were positive and significant in improving student learning outcomes. Dominant learning creativity in determining student learning outcomes. Students' creativity is directed to have curiosity, have high discipline, often ask questions, be independent, listen to material, think critically and periodically, take initiative and have broad memory and insight. The implementation of the Contextual Teaching and Learning approach helps students to be active in learning, increase knowledge, increase understanding, practice the material and reflect on each knowledge to achieve the results of the learning process.